Study of distal arrangement of common bile duct and pancreatic duct according to distal classification in choledochal cyst - Uddagiri, Sasikanth; Thumma, Venumadhav; Nekarakanti, Phani Kumar; Gunturi, Suryaramachandra V.; Muddamsetty, Madhulika; Nagari, Bheerappa (International Surgery Journal, 2025)
Background: Most widely accepted classification for choledochal cyst was Todani classification. In which, Distal extent of choledochal cyst and its resection was not clearly defined. So, this distal classification may be supplementary in guiding distal extent of cyst and its resection in various types of choledochal cysts. Methods: This was a prospective observational study done in surgical gastroenterology at Nizams Institute of Medical Sciences, Hyderabad. All patients radiologically diagnosed as choledochal cysts were included. Patients with malignant distal bile duct stricture, refused to participate were excluded. Distal arrangement of all patients were interpreted in magnetic resonance cholangiopancreatography (MRCP) and classified distally. Results: In the present study of 44 patients, median age was 39 years with female preponderance. Median cyst diameter was 20.5 mm. Most common types were Todani I and distal I followed by other subtypes. Conclusions: Distal type I was the most common arrangement. So, extensive intrapancreatic dissection may be avoided to prevent dreadful complications like pancreatic fistula. Studies with larger sample and correlation with postoperative pancreatic complications should be done further.